Native tree regeneration in native tree plantations: understanding the contribution of Araucaria angustifolia to biodiversity conservation in the threatened Atlantic Forest in Argentina - Medina, Micaela; Pérez Flores, Magalí; Goya, Juan Francisco; Campanello, Paula Inés; Pinazo, Martin Alcides; Ritter, Luis Javier; Arturi, Marcelo Fabian (Wiley, 2020)
Deforestation is a global process that has strongly affected the Atlantic Forest in South America, which has been recognised as a threatened biodiversity hotspot. An important proportion of deforested areas were converted to forest plantations. Araucaria angustifolia is a native tree to the Atlantic Forest, which has been largely exploited for wood production and is currently cultivated in commercial plantations. An important question is to what extent such native tree plantations can be managed to reduce biodiversity loss in a highly diverse and vulnerable forest region. We evaluated the effect of stand age, stand basal area, as a measure of stand density, and time since last logging on the density and richness of native tree regeneration in planted araucaria stands that were successively logged over 60 years, as well as the differences between successional groups in the response of plant density to stand variables. We also compared native tree species richness in planted araucaria stands to neighbouring native forest. Species richness was 71 in the planted stands (27 ha sampled) and 82 in native forest (18 ha sampled) which approximate the range of variation in species richness found in the native forests of the study area. The total abundance and species richness of native trees increased with stand age and time since last logging, but ecological groups differed in their response to such variables. Early secondary trees increased in abundance with stand age 3–8 times faster than climax or late secondary trees. Thus, the change in species composition is expected to continue for a long term. The difference in species richness between native forest and planted stands might be mainly explained by the difference in plant density. Therefore, species richness in plantations can contribute to local native tree diversity if practices that increase native tree density are implemented.